Advances in protective layer-coating on metal nanowires with enhanced stability and their applications. (March 2021) - Bang, Junhyuk; Coskun, Sahin; Pyun, Kyung Rok; Doganay, Doga; Tunca, Sensu; Koylan, Serkan; Kim, Dongkwan; Unalan, Husnu Emrah; Ko, Seung Hwan
Highlights: Metal nanowire transparent electrode is the best candidate to replace fragile ITO. Metal nanowire still has chemical/mechanical stability problem. To enhance stability, core-shell type metal nanowires have been developed. Advances in the core-shell metal nanowires with enhanced stability are highlighted. The prospects and challenges of core-shell metal nanowires were addressed. Abstract: The demand for flexibility in transparent conductive electrodes(TCEs) is increasing due to the functionality demand and convenience of deformable electrodes. The high-cost and brittleness of the conventional indium tim oxide (ITO) films are obstacles to their utilization in TCEs. Metal nanowires are highly promising as substitutes for ITO. Metal nanowire electrodes achieved high-conductivity, high-transparency, and high-stretchability through the development of fabrication technology. Nevertheless, it is challenging to prevent their degradation by the external environment, intensive investigations that can improve the stability are required. Among measures to improve stability, a protective-layer coating on metal nanowires is shown to be a very effective way. Therefore, it is essential to organize the development of protective layer-coating. This review compiles coating methods of stable materials (overall coverage coating, core-shell coating, junction enhancement coating), and the obtained TCE performances. Electrical properties such as sheet resistance, transmittance conjunction with the enhanced stability are discussed. Finally, the recent progress in TCE applications based on improved stability metal nanowires are discussed concisely. Various applications of improved stability nanowires such as solar-cell, supercapacitor, and transparent heaters are considered and their performances as well as fabrication protocols are disclosed. Graphical abstract: Image, graphical abstract